"Putting gender on the table": Understanding reactions to women who discuss gender inequality. (August 2018) - Anisman-Razin, Moran; Kark, Ronit; Saguy, Tamar
Even though gender inequality remains an important challenge across societies, many believe it to be long gone (Marken, 2016). Thus, it is essential to publicly address issues related to gender inequality as a first step towards advancing change in this domain. However, those who address gender inequality may encounter personal costs. In the current research, we examined reactions to women who "put gender on the table." In Study 1 ( N = 202), men who were exposed to a woman who raised the issue of gender inequality (vs. age inequality or a neutral topic), had more negative attitudes towards both her and gender equality. In Study 2, ( N = 233), women high on feminist identification were more positive toward a woman who discussed gender inequality (vs. other topics), whereas women low on feminist identification were more negative toward both her and the issue. Theoretical and practical implications are discussed.